Implementation trial of a cognitive behavioural therapy programme for reducing student stress in the final year of secondary school. (26th September 2021) - Jagiello, Tess; Wuthrich, Viviana M.; Ellis, Louise A.
Abstract : The final year of secondary school has been shown to be associated with heightened student stress. Psychological interventions have been shown to be effective in reducing and preventing distress in students during this school period, although the widespread adoption of these interventions into school settings is limited. There have been recent calls for research to examine the implementation success of evidence‐based programmes when used by schools in school settings. The present study aimed to evaluate the implementation success of an evidence‐based cognitive‐behavioural therapy programme (Study without Stress) using the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE‐AIM) framework. At one Australian high school, all tutor group teachers were trained by the school counsellor to deliver the programme in standard school classes to students in the lead up to their final year of secondary school. Students ( n = 80) and teachers ( n = 11) reported on programme success against the RE‐AIM framework at pre‐intervention, post‐intervention, and three‐month follow‐up. The findings indicated that SWOS was implemented successfully by the school. SWOS was associated with maintaining student stress levels at normal levels over time, as well as reducing the severity of stress for initially highly distressed students. The findings provide evidence from implementation science that SWOS can be adapted and delivered effectively by school staff to manage stress in final year secondary school students.